Models of Asynchronous Parallel Nonlinear Multisplitting Relaxed Iterations (Journal of Computational Mathematics, 2021)
In the sense of the nonlinear multisplitting and based on the principle of sufficiently using the delayed information, we propose models of asynchronous parallel accelerated overrelaxation iteration methods for solving large scale system of nonlinear equations. Under proper conditions, we set up the local convergence theories of these new method models.